2018
DOI: 10.1371/journal.pntd.0006279
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic placental infection by non-falciparum Plasmodium spp.

Abstract: BackgroundAmong the Plasmodium species that infect humans, adverse effects of P. falciparum and P. vivax have been extensively studied and reported with respect to poor outcomes particularly in first time mothers and in pregnant women living in areas with unstable malaria transmission. Although, other non-falciparum malaria infections during pregnancy have sometimes been reported, little is known about the dynamics of these infections during pregnancy.Methods and findingsUsing a quantitative PCR approach, bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
2
7
2
Order By: Relevance
“…RDT LODs widely vary, sometimes even within the same country as has been observed in Angola 6. Second, non- P. falciparum malaria is not detected by commonly used PfHRP2-based RDTs 7. Third, improper RDT storage, including prolonged exposure to hot or humid conditions, can impair RDT performance 8.…”
Section: Introductionmentioning
confidence: 99%
“…RDT LODs widely vary, sometimes even within the same country as has been observed in Angola 6. Second, non- P. falciparum malaria is not detected by commonly used PfHRP2-based RDTs 7. Third, improper RDT storage, including prolonged exposure to hot or humid conditions, can impair RDT performance 8.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular surveillance has demonstrated that non-falciparum malaria has been underestimated by microscopy diagnosis [2][3][4][5] , and rapid diagnostic tests (RDT), which are unable to diagnose non-falciparum malaria to the species level 6,7 . Molecular studies are beginning to demonstrate alarmingly high levels (4-24%) of P. malariae mono-and co-infections across continents 2,[8][9][10][11][12] . P. malariae infections commonly present with mild or no symptoms, however, severe disease, including anaemia, renal pathologies, and splenomegaly [13][14][15][16][17] can occur, complications which can prove fatal 16 .…”
mentioning
confidence: 99%
“…Among the five known species of Plasmodium that infect humans, Pf infection (and to a lesser extent Po and Pm) is the essential cause of malaria burden in tropical Africa ( World Health Organization [WHO], 2018b ). In West Africa, both Po and Pm malaria cases have been identified in Benin, Ghana, and Senegal ( Browne et al, 2000 ; Roucher et al, 2014 ; Trape et al, 2014 ; Doritchamou et al, 2018 ), as well as Po in Cote d’Ivoire and Comoros Islands ( Bauffe et al, 2012 ), to mention a few. However, there have been no information publicly reported yet on Po and Pm from Togo.…”
Section: Discussionmentioning
confidence: 99%